Ultra-fast vortex motion in a direct-write Nb-C superconductor - O. V. Dobrovolskiy; D. Yu Vodolazov; F. Porrati; R. Sachser; V. M. Bevz; M. Yu Mikhailov; A. V. Chumak; M. Huth (Nature Communications, 2020)
To realize ultra-fast dynamics of superconducting vortices one needs to overcome the practical issue of flux-flow instability (FFI). Here, Dobrovolskiy et al. demonstrate ultra-fast vortex motion at 10-15 km/s velocity in a Nb-C superconductor where the FFI is described by the edge-controlled FFI model.